1976
DOI: 10.1520/jfs10497j
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Analysis by Energy Dispersive X-Ray: A Significant Factor in the Forensic Analysis of Glass

Abstract: Comparison of glass particles by the forensic scientist is routinely accomplished by measuring some physical properties. Direct comparison of densities ϱ and refractive indexes (ͻC, ͻD, and ͻF being the refractive indexes determined at 6563, 5893, and 4861 nm, respectively) are the most widely used physical measurements because of convenience, reproducibility, sensitivity, and applicability to small sample size. Traditionally, if the physical comparison showed significant difference, it was concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, it may be desirable in some cases to characterise the glass fragments further. Methods that have been suggested include examination of the surface of the glass to determine whether it is flat or curved [4,5], the examination of the elemental composition [6][7][8][9][10][11][12][13][14], and the examination of the change in refractive index upon annealing [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be desirable in some cases to characterise the glass fragments further. Methods that have been suggested include examination of the surface of the glass to determine whether it is flat or curved [4,5], the examination of the elemental composition [6][7][8][9][10][11][12][13][14], and the examination of the change in refractive index upon annealing [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies, it was found that elemental analysis techniques could successfully be employed in conjunction with RI to discriminate between samples, where RI data alone could not. Such studies utilized spectrophotometric techniques including SEM‐EDX (7–9), EDXRF (8,10), μ‐XRF (8), ICP‐AES (10–12), and mass spectrometric techniques including ICP‐MS (8,13,14), LA‐ICP‐MS (15), and time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS).…”
mentioning
confidence: 99%
“…The authors compared elemental ratios, such as Zn/Ca, As/Ca, and Sr/Ca as a means for discrimination. Results from this study demonstrate that combining refractive index measurements with elemental analysis techniques is a powerful combination that allows for more discrimination than by using refractive index alone [7].…”
Section: Traditional Methods Of Forensic Glass Analysismentioning
confidence: 88%
“…Many of these reports describe elemental analyses such as laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and inductively coupled mass spectrometry (ICP-MS) [2][3][4][5], time of flight secondary ion mass spectrometry (TOF-SIMS) [6],scanning electron microscopy equipped with energy dispersive spectroscopy (SEM-EDS) [7] , and phosphorescence [8].…”
Section: Traditional Methods Of Forensic Glass Analysismentioning
confidence: 99%